« Retail the coda » : le retour au sonnet dans l’œuvre récente de Geoffrey Hill - Carole Birkan-Berz (Revue LISA, 2009)
Up until Tenebrae, the sonnet had been given a prominent place in Geoffrey Hill’s work. Relying on a slightly modernised form harking back to the Renaissance, Hill used it as a vehicle for metaphysical questioning on the nature of poetry, violence or religion. In more recent volumes, however, the form seemed to have disappeared, only to survive in a palimpsestic way. Surprisingly, Hill’s last two collections feature a return to the sonnet, with its twin themes of amorous discourse and political eloquence. Though for the most part shunning rhyme and rigid stanzaic format, the sonnets retain syllabic lines and a dialectical structure typical of the genre. The flexible placing of the volta, the use of a coda, as well as some of the thematics following on from The Orchards of Syon, point to Milton as Hill’s main influence, as well as to Coleridge and Wordsworth, as practitioners of the political sonnet. Moreover, the appearance of the autobiographical lyric ‘I’ in these sonnets as in recent collections points to the persistence of a Romantic ethos, of which the poet had been suspicious in his early writing. The sonnet, with a fresh autobiographical ‘I’ and a renewed political dimension, thus re-anchors Hill in a Romantic tradition.